Consumer behavior in the circular economy: Developing a product-centric framework. (15th January 2023) - Shevchenko, Tetiana; Saidani, Michael; Ranjbari, Meisam; Kronenberg, Jakub; Danko, Yuriy; Laitala, Kirsi
Abstract: The operationalization of circular economy (CE) strategies requires consumer involvement in the acquisition, use, and disposal of products and services. However, encouraging sustainable consumption patterns and CE-oriented consumer behavior to enable the CE in practice is complex and in its infancy stage. This study aims to clarify, frame, and measure consumer contributions to the implementation of the CE in regard to the 10R circular strategies: recover, recycle, repurpose, remanufacture, refurbish, repair, re-use, reduce, rethink, and refuse. The study employs a semi-systematic literature review and a conceptual analysis to develop an inclusive framework of consumer behaviors relating to CE perspectives in practice. The manuscript addresses three goals. First, a tri-dimensional consumer role in contributing to the CE transition is mapped, considering the consumer as (i) a product customer who acquires products or services, (ii) a product user who retains the value of products, and (iii) an end-of-life product holder who discards products. Framing this tri-dimensional contribution is essential to closing the loop on products through (i) careful use and maintenance, (ii) proper collection, and (iii) reuse, repair, or recycling. Second, based on the "closing–slowing and future–past" matrix developed, a CE-related product typology involving fifteen circular product categories is proposed. Third, a five-level hierarchical pyramid for CE-related products is presented to rank the fifteen circular product categories identified from more circular to less circular. Thus, five levels of consumer contributions to the CE, from low to high, are defined as corresponding to the circular product categories identified. As a result, a novel product-centric framework of CE-related consumer behavior to monitor and measure product-level consumer contributions to the CE is developed. The resulting conceptual framework opens up further perspectives for policymakers and producers to more effectively manage the process of directing consumer behavior toward more circular and sustainable consumption alternatives. Graphical abstract: Image 1